Elevation of Preprocedural Systemic Immune Inflammation Level Increases the Risk of Contrast-Associated Acute Kidney Injury Following Coronary Angiography: A Multicenter Cohort Study - Lai W; Zhao X; Huang Z; Xie Y; Yu S; Tu J; Guo D; Xiu J; Mai Z; Li Q; Huang H; Li H; et al. (Dove Medical Press, 2022)
Wenguang Lai,1,2,* Xiaoli Zhao,3,* Zhidong Huang,1,* Yun Xie,1,2,* Sijia Yu,1,4 Jiabin Tu,5 Dachuan Guo,6 Jiaming Xiu,5 Ziling Mai,1,2 Qiang Li,1 Haozhang Huang,1,4 Huanqiang Li,1 Jun-Yan Xu,1,7 Hongyu Lu,1 Guanzhong Chen,1 Shiqun Chen,1 Jin Liu,1 Yong Liu1 1Department of Guangdong Provincial Key Laboratory of Coronary Heart Disease Prevention, Guangdong Cardiovascular Institute, Guangdong Provincial People's Hospital, Guangdong Academy of Medical Sciences, Guangzhou, 510080, People's Republic of China; 2School of Biology and Biological Engineering, South China University of Technology, Guangzhou, People's Republic of China; 3Department of Cardiology, The Third Affiliated Hospital of Sun Yat-sen University, Guangzhou, People's Republic of China; 4The Second School of Clinical Medicine, Southern Medical University, Guangzhou, People's Republic of China; 5Department of Cardiology, Longyan First Affiliated Hospital of Fujian Medical University, Longyan, 364000, People's Republic of China; 6Department of Cardiology, Sun Yat-sen Memorial Hospital, Sun Yat-sen University, Guangzhou, Guangdong, People's Republic of China; 7Ministry of Education, Key Laboratory of Hainan Trauma and Disaster Rescue, College of Emergency and Trauma, Hainan Medical University, Haikou, 571199, People's Republic of China*These authors contributed equally to this workCorrespondence: Yong Liu; Jin Liu, Department of Guangdong Provincial Key Laboratory of Coronary Heart Disease Prevention, Guangdong Cardiovascular Institute, Guangdong Provincial People's Hospital, Guangdong Academy of Medical Sciences, Guangzhou, 510080, People's Republic of China, Email liuyong@gdph.org.cn; ljaw397017568@163.comBackground: Inflammation and immune responses play an important role in the pathophysiology of contrast-associated acute kidney injury (CA-AKI), and systemic immune inflammation index (SII) has recently emerged as a new parameter for immune and inflammatory response evaluation. However, limited research has been undertaken to explore the relationship between SII and CA-AKI following coronary angiography (CAG).Patients and Methods: From January 2007 to December 2020, 46,333 patients undergoing CAG were included from 5 Chinese tertiary hospitals. SII was calculated as total peripheral platelets count × neutrophil-to-lymphocyte ratio. Patients were categorized by preprocedural SII quartiles: Q1 ≤ 404.5, Q2 > 404.5 and ≤ 631.7, Q3 > 631.7 and ≤ 1082.8, Q4 > 1082.8. Univariable and multivariable logistic regression were used to reveal the link between preprocedural SII and CA-AKI.Results: A total of the 46,333 patients (62.9 ± 11.5 years, female 28.1%) were included in the study. The incidence of CA-AKI was 8.4% in Q1 group, 8.7% in Q2 group, 9.4% in Q3 group, 15.1% in Q4 group. In the multivariable model, comparing the highest (Q4 group) to lowest (Q1 group) SII level categories, preprocedural SII was related to a higher risk of CA-AKI after fully adjusting for well-known confounders, and there was no statistically difference in the other two SII level categories (Q2 and Q3 groups) compared with Q1 group (adjusted model 3: Q2 group: OR: 0.98, 95% CI: 0.87- 1.11, P = 0.771; Q3 group: OR: 1.04, 95% CI: 0.92- 1.18, P = 0.553; Q4: OR: 1.65, 95% CI: 1.45- 1.88, p < 0.001; P for trend < 0.001). Similar results were found for all the subgroups analysis except for patients undergoing PCI, and the interaction analyses for age, PCI and AMI were significant. In addition, Kaplan-Meier curves demonstrated that the lowest quartile group showed the worst all-cause mortality in a significant SII level-dependent manner among the four groups (Log rank test; p < 0.0001).Conclusion: Elevated preprocedural SII level was a significant and independent risk factor for CA-AKI following CAG. Higher-quality prospective studies are needed to validate the predictive value of SII for CA-AKI.Keywords: systemic immune inflammation index, contrast-associated acute kidney injury, coronary angiography, preprocedural